Integrating Stamping-Induced Material Property Variations into FEM Models for Structural Performance Simulation of Sheet-Metal Components - Burello Elia; Hamed Rezvanpour; Dario Cimolino; Francesco Capaccioli; Alberto Vergnano (Applied Sciences, 2025)
The accurate prediction of structural performance in sheet-metal components is critical for optimizing design and ensuring reliability in engineering applications. This study emphasizes the necessity of incorporating non-uniformities induced by stamping processes, such as thickness variation and work-hardening effects, into Finite Element Method (FEM) simulations. Experimental and computational analyses reveal that neglecting these variations results in significant discrepancies, particularly in displacement predictions, where deviations exceeding 50% were observed at specific points. While elastic behavior showed reasonable agreement with experimental results, plastic deformation predictions were notably less accurate due to the inherent inhomogeneities of the real work-hardening model compared to the uniform assumptions in standard FEM models. These findings underscore the need for improved methodologies in mapping stamping-induced material properties and validating simulation results. Further refinement of mapping accuracy and validation techniques is essential for enhancing the predictive capabilities of FEM simulations for complex sheet-metal components.